IMPLEMENTING DIGITAL ACCOUNTING INFORMATION SYSTEMS TO ENHANCE FINANCIAL GOVERNANCE IN VILLAGE-OWNED ENTERPRISES (BUMDES): EVIDENCE FROM WEST LOMBOK, NTB - Indriani, Eni; Martiningsih, Rr. Sri Pancawati; Inapty, Biana Adha (Jurnal Aplikasi Akuntansi, 2025)
This study analyzes the implementation of digital accounting information systems to strengthen financial governance in Village-Owned Enterprises (BUMDes) in West Lombok Regency, Indonesia. The research explores user readiness, perceived usefulness, and ease of use in adopting digital financial systems using the Rapid Application Development (RAD) method integrated with the Technology Acceptance Model (TAM). A qualitative-descriptive approach was employed, combining pre-tests, post-tests, field observations, and in-depth interviews with BUMDes managers, village facilitators, and development advisors. The findings reveal that introducing digital accounting systems significantly improved financial reporting accuracy, transparency, and timeliness, particularly among BUMDes with proactive leadership and higher digital literacy. The TAM analysis confirms that perceived usefulness and ease of use strongly influence user acceptance and continued utilization of digital systems, while organizational support and training serve as critical mediating factors. The study demonstrates that digitalization enhances accountability and operational efficiency from a governance perspective, but sustainable transformation requires continuous human resource development through structured education and technical mentoring. Theoretically, this research contributes to extending the TAM framework within community-based financial institutions, illustrating the socio-technical nature of digital transformation in rural contexts. Practically, the results emphasize the need for integrated policy support, including standardized reporting templates, digital infrastructure provision, and incentive-based training for BUMDes managers. Future studies should adopt a longitudinal and mixed-method approach to evaluate long-term impacts and financial performance outcomes.